VD_FINDINFO Décision / 2012 / 439 vom 4. Januar 2012 - VD Tribunal cantonal (2012)
CONTRAVENTION DE POLICE DE DROIT CANTONAL, CONTRAVENTION, OPPOSITION TARDIVE | 356 CPP (CH), 357 al. 1 CPP (CH), 357 al. 2 CPP (CH), 393 al. 1 let. b CPP (CH), 395 let. a CPP (CH)